PENGARUH CURRENT RATIO, RETURN ON EQUITY DAN EARNING PER SHARE TERHADAP HARGA SAHAM PADA PERUSAHAAN INDEKS LQ45 SEKTOR MINING & FINANCE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Hanifah Hanifah; M. Roni Saekhu (Jurnal Studia Akuntansi dan Bisnis (The Indonesian Journal of Management & Accounting), 2022)
This study is based on investor demand for the company's financial performance. The company's financial performance is used by investors as a measuring tool before they invest and reflects the value of the stock price of a company. The company's financial performance can be seen through financial ratios which include Current Ratio, Return on Equity and Earning Per Share.This study aims to empirically examine the effect of CR, ROE and EPS either simultaneously or partially on stock prices in the LQ45 index companies in the Mining and Finance sector listed on the Indonesia Stock Exchange for the 2016-2020 period.The data used in this study were obtained from secondary data in the form of annual financial statements of LQ45 index companies in the Mining and Finance sector listed on the Indonesia Stock Exchange for the 2016-2020 period. The sample that meets the criteria is 9 companies using purposive sampling technique with a total data of 45.This study uses multiple linear regression analysis with the tool used is SPSS version 25 software. The results of the analysis show that partially CR has no significant effect on stock prices, ROE has no significant effect on stock prices, EPS has a significant effect on stock prices. Meanwhile, simultaneously Current Ratio (CR), Return On Equity (ROE) and Earning Per Share (EPS) have an influence on stock prices. The practical implication of this research is that it can be used for investors as a guide for investing and for companies as a guide for providing information for potential investors.